COMPARISON OF CLINICOPATHOLOGICAL AND SURVIVAL ANALYSIS OF ENDOMETRIAL DEDIFFERENTIATED, UNDIFFERENTIATED CARCINOMAS AND CARCINOSARCOMAS - Usman Hassan,; Iram Asrar,; Hina Maqbool,; Mudassar Hussain,; Maryam Hameed,; Asif Loya, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Endometrial cancer ranks as the sixth frequently detected cancer and the 14th highest contributor, to cancer-related fatalities, among women globally. High-grade endometrial carcinomas encompass a diverse array of clinically aggressive tumors, including FIGO grade 3 endometrioid adenocarcinoma, uterine papillary serous carcinoma (UPSC), clear cell carcinoma, undifferentiated carcinoma, dedifferentiated carcinoma, and carcinosarcoma. The classification and diagnosis of these tumors pose challenges due to the absence of well-established molecular markers or panels The main purpose of this study is to assess and compare the clinicopathological characteristics of and survival rates of undifferentiated endometrial carcinoma (UEC), dedifferentiated carcinoma (DEC), and carcinosarcoma (CS) in the Pakistani population at SKMCH&RC. Methods: All patients diagnosed with DEC, UEC, and CS were analyzed from January 2011 and December 2022. Clinicopathological and survival data was retrospectively reviewed and analyzed using SPSS version 27. Kaplan-Meier analysis was used to calculate overall survival (OS) and disease-free survival (DFS). Results: Among 71 selected patients, 47.9% had CS, 29.6% had DEC, and 22.5% had UEC. Mean±S.D age at diagnosis was 58.18±11.35 years. A statistically significant association of DEC, UEC, and CS was identified (p-value <0.05) with myometrial invasion (p=0.02), lymphovascular invasion(p=0.006), positive margins(p=0.003), and involvement of adnexa/ parametria/ vaginal /other organ (p=0.01). The commonest pathological stage was pT1 38(53.5%). 56.3% of patients received chemotherapy, 29.6% received radiotherapy, and 38.0% received a combination of chemotherapy and radiation treatment. Recurrence occurred in 19.7% and death occurred in 37.7% of patients. The highest 5-year OS rate for pathological stage 1 was 59.1% (95% C.I: 42.9-81.3%) and 5-year-DFS was 62.2% (95% C.I: 42.9-81.3%). Conclusion: Patients diagnosed at an early pathological stage demonstrate better survival outcomes compared to an advanced stage, as documented in previous studies. Nevertheless, survival rates remain lower than Western population, indicating a necessity for gathering additional clinical data and alter the management strategies in our population.